Evaluating The Impact of Viral Marketing Elements in TV Ads on Brand Awareness in Indonesia’s Dairy Industry - Thio Tryphena, Grace; Novianti, Afdelia; Maharani, Agystiara; Mustikasari, Faranita (Dinasti Publisher, 2026)
This study examines the effectiveness of television advertising in increasing brand awareness for dairy products within the Fast-Moving Consumer Goods (FMCG) sector in Indonesia. Even in today’s digital advertising era, television remains a crucial part of advertising strategies, particularly among traditional audiences who continue to rely on conventional TV channels. By examining several elements of viral marketing, such as credibility, entertainment, informativeness, and irritation, this study analyzes how consumer perceptions of TV advertising influence brand awareness. The analysis using a structural modeling approach indicates that the model exhibits good convergent and discriminant validity, with all indicators having outer loadings above 0.7 and construct reliability, as indicated by Composite Reliability values above 0.7. Adjusted R-squared indicates that the model adequately explains 50.5% of the variance in Ad Value (AV) and 57.9% in Brand Awareness (BA). Hypothesis testing indicates that credibility and entertainment significantly impact Ad Value, which in turn influences Brand Awareness. However, informativeness and irritation were found to have no significant effect. These findings highlight the importance of credibility and entertainment in driving brand awareness among dairy consumers and reinforce the role of television advertising as a still influential communication medium in the Indonesian market.